Individual Income Macroeconomic Factors Dictate Household Consumption In Bogor Regency: Faktor Makroekonomi Pendapatan Individu Menentukan Konsumsi Rumah Tangga Kabupaten Bogor - Laluna Nandita Hapsari; Marseto Marseto (Academia Open, 2026)
General Background Household consumption constitutes a critical component for evaluating national economic stability and aggregate demand. Specific Background Within the administrative boundaries of Bogor Regency, individual spending serves as a vital proxy for assessing community purchasing power amidst fluctuating regional conditions. Knowledge Gap Previous macroeconomic literature predominantly examines consumption patterns at the national or provincial scale, leaving the distinct economic dynamics of specific district-level buffer zones largely under-studied. Aims This study analyzes the relationship between inflation, individual earnings, the economic growth rate, and community spending in Bogor Regency from 2011 to 2024. Results Utilizing multiple linear regression on a 14-year time series dataset, the analysis reveals that individual earnings significantly and positively determine spending levels, whereas inflation and economic expansion rates show no significant partial correlation. Novelty This research specifically isolates and quantifies the dominant role of individual earnings over broader macroeconomic indicators in dictating purchasing capacity within a heterogeneous administrative territory. Implications Regional policymakers must prioritize initiatives that stimulate real wage generation, such as job creation and productivity support, to sustainably secure community purchasing capacity. Highlights Individual earnings significantly direct the purchasing capacity of regional populations. Regional inflation and economic expansion rates demonstrate no significant statistical correlation with buyer capability. Administrative frameworks must prioritize direct job creation and real wage generation to sustain community spending. Keywords Macroeconomic Indicators; Regional Earnings; Household Spending; Purchasing Capability; Capital Buffer Zone